Using Bloom - Zainul Arifin; Suci Ramadhanti Febriani; Anasruddin Anasruddin (Universitas Islam Negeri Palangka Raya, 2021)
Learning Arabic writing skills in the Pandemic Era is confronted with complex problems. One of complex problems is the minimal interaction of the limitations in learning process that has an impact on students